Indian Journal of Nematology 13(2):1983 (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1981-83) Chief Editor - E KHAN, Nematology Divn., I. A. R. I., New Delhi  Members    -ABRAR M. KHAN, Botany Dept., A. M. V., Aligarh                         - A.R. SESHADRI, I. A. R. I., New Delhi                         - V M. DAS, Zoology Dept., Osmania Univ., Hyderabad                          - S.N. DAS, Nematology Dept., O. V. AT., Bhubaneshwar                         - C.V. SIVAKUMAR, Nematology Dept., T.N.A.V., Coimbatore                         - Q.H. BAQRl, Z. S. I., Calcutta                          - GOPAL SWAKUP, Nematology Divn., I. A. R. I., New Delhi